A Pivotal Role for Thiamine Deficiency in the Expression of Neuroinflammation Markers in Models of Alcohol‐Related Brain Damage. (20th January 2019) - Toledo Nunes, Polliana; Vedder, Lindsey C.; Deak, Terrence; Savage, Lisa M.
Abstract : Background: Alcohol‐related brain damage (ARBD) is associated with neurotoxic effects of heavy alcohol use and nutritional deficiency, in particular thiamine deficiency (TD), both of which induce inflammatory responses in brain. Although neuroinflammation is a critical factor in the induction of ARBD, few studies have addressed the specific contribution(s) of ethanol (EtOH) versus TD. Methods: Adult rats were randomly divided into 6 conditions: chronic EtOH treatment (CET) where rats consumed a 20% v/v solution of EtOH for 6 months; CET with injections of thiamine (CET + T); severe pyrithiamine‐induced TD (PTD); moderate PTD; moderate PTD during CET; and pair‐fed controls. After the treatments, the rats were split into 3 recovery phase time points: the last day of treatment (time point 1), acute recovery (time point 2: 24 hours posttreatment), and delayed recovery (time point 3: 3 weeks posttreatment). At these time points, vulnerable brain regions (thalamus, hippocampus, frontal cortex) were collected and changes in neuroimmune markers were assessed using a combination of reverse transcription polymerase chain reaction and protein analysis. Results: CET led to minor fluctuations in neuroimmune genes, regardless of the structure being examined. In contrast, PTD treatment led to a profound increase in neuroimmune genes and proteins within the thalamus. Cytokine changes in the thalamus ranged in magnitude from moderate (3‐fold and 4‐fold increase in interleukin‐1β [IL‐1β] and IκBα) to severe (8‐fold and 26‐fold increase in tumor necrosis factor‐α and IL‐6, respectively). Though a similar pattern was observed in the hippocampus and frontal cortex, overall fold increases were moderate relative to the thalamus. Importantly, neuroimmune gene induction varied significantly as a function of severity of TD, and most genes displayed a gradual recovery across time. Conclusions: These data suggest an overt brain inflammatory response by TD and a subtle change by CET alone. Also, the prominent role of TD in the immune‐related signaling pathways leads to unique regional and temporal profiles of induction of neuroimmune genes. Abstract : Thiamine deficiency (TD) and Chronic Ethanol Treatment (CET) are critical factors in the induction of Alcohol‐Related Brain Damage (ARBD) and neuroinflammation in the brain. The goal of this study was to determine the effect of CET and TD on the expression of several key neuroimmune genes in brain regions vulnerabilities to ARBD. Our findings show the TD, rather than CET, can be considered a key driver of neuroimmune gene expression and subsequent neuroinflammation.